Impact of combined management strategies of monensin and virginiamycin in high energy diets on ruminal fermentation and nutrients utilization - Dellaqua, João V. T. [UNESP]; Rigueiro, André L. N. [UNESP]; Silvestre, Antonio M. [UNESP]; Pereira, Murilo C. S. [UNESP]; Felizari, Luana D. [UNESP]; Demartini, Breno L. [UNESP]; Dias, Evandro F. F. [UNESP]; Silva, Leandro A. F. [UNESP]; Casali, Daniel M. [UNESP]; Souza, Katia L. R. [UNESP]; Souza, Johnny M. [UNESP]; Millen, Danilo D. [UNESP] (Frontiers, 2024)
Feed additives such as monensin (MON) and virginiamycin (VM) are commonly utilized in feedlot diets to enhance rumen fermentation. Nevertheless, the precise effects of combining MON and VM during specific feedlot periods and the advantages of this combination remain unclear. This study was designed to investigate the effects of withdrawal of MON when associated with VM during the adaptation and finishing periods on ruminal metabolism, feeding behavior, and nutrient digestibility in Nellore cattle. The experimental design was a 5 × 5 Latin square, where each period lasted 28 days. Five rumen-cannulated Nellore yearling bulls were used (414,86 ± 21,71 kg of body weight), which were assigned to five treatments: (1) MON during the entire feeding period; (2) VM during the entire feeding period; (3) MON + VM during the adaptation period and only VM during the finishing period 1 and 2; (4) MON + VM during the entire feeding period; (5) MON + VM during the adaptation and finishing period 1 and only VM during the finishing period 2. For the finishing period 1, animals fed T3 had improved potential degradability of dry matter (p = 0.02). Cattle fed T3 and T5 had the highest crude protein degradability when compared to animals receiving T2 (p = 0.01). Animals fed T2 and T3 had reduced the time (p < 0.01) and area under pH 6.2 (p = 0.02). Moreover, animals fed T4 had greater population of protozoa from the genus Diplodinium (p = 0.04) when compared to those from animals fed T2, T3 and T5. For the finishing period 2, animals fed T3 had greater starch degradability when compared to animals receiving T4 and T5 (p = 0.04). Animals fed T3, T4 and T5 had increased the duration of time in which pH was below 5.6 (p = 0.03). The area under the curve for ruminal pH 5.2 and pH 5.6 was higher for the animals fed T3 (p = 0.01), and the area under pH 6.2 was higher for the animals fed T3 and T5 (p < 0.01) when compared to animals receiving T2. There is no substantial improvement on the rumen fermentation parameters by the concurrent utilization of MON and VM molecules, where the higher starch and protein degradability did not improve the rumen fermentation.
Keywords: feed additive; feedlot; ionophore; metabolism; rumen